Endoscopic hemostasis using gel immersion endoscopy for duodenal ulcer and a sigmoid colon polyp: A novel gel injection method. Issue 11 (23rd September 2022) - Jinushi, Ryuhei; Tashima, Tomoaki; Ishii, Naoki; Fujita, Akashi; Tanisaka, Yuki; Mizuide, Masafumi; Mashimo, Yumi; Kawasaki, Tomonori; Ryozawa, Shomei
Abstract: Gel immersion endoscopy (GIE) has gained prominence for securing a good visual field. Traditionally, OS‐1 jelly (Otsuka Pharmaceutical Factory) has been used for GIE. However, due to the presence of electrolytes, it is unsuitable for endoscopic hemostasis using a monopolar device. Therefore, VISCOCLEAR (Otsuka Pharmaceutical Factory), a new gel that does not contain electrolytes, has been developed. Moreover, unlike water or saline, VISCOCLEAR does not readily mix with blood, making it effective in visualizing gastrointestinal bleeding. We report two cases in which GIE was performed using a novel gel injection method. Abstract : Gel immersion endoscopy (GIE) has gained prominence for securing a good visual field. Traditionally, OS‐1 jelly has been used for GIE. However, due to the presence of electrolytes, it is unsuitable for endoscopic hemostasis using a monopolar device. Therefore, VISCOCLEAR, a new gel that does not contain electrolytes, has been developed.